Self-regulated learning and language achievement among CELPAD students at IIUM University - Yasmine, Chafai (Kulliyyah of Education, International Islamic University Malaysia, 2017)
English language learners (ELL) need to learn English to be able to access the academic content. Although ELL may be able to communicate effectively in everyday situations, they may struggle to acquire the language of instruction which impacts their academic performance in the university. Therefore, this study aimed to examine the relationship between Self-regulated learning and language achievement among language learners in a public university in Malaysia and to describe the SRL strategies used by a high achieving English language learner. A mixed method research method was employed. In phase 1, data was collected via the Motivated Strategies for Learning Questionnaire. The population of the study was students from the Center for Languages and Pre-University Academic Development (CELPAD). 220 participants for this study were selected through a randomized sampling method. SPSS software (version 20) was run to analyze the data using descriptive and inferential analysis. The results of the first phase showed that there is a small positive relationship between SRL and language achievement (r= .141). In regard to SRL and demographic variables, the analysis showed no significant differences between gender, English levels, undergraduate and post graduate students, and non-Malaysian and Malaysian students in terms of using SRL. In phase 2, the Self-Regulated Learning Interview Schedule (SRLIS) was used, and a case study design was employed through a semi-structured interview with one 21 years old female who is learning English. Six emergent themes were found: cognitive strategies, cooperation with friends/classmates, communication between student and teacher, using multiple sources, overcoming the difficulties, and seeking help from friends. Further research is recommended in various contexts regarding the phenomenon of SRL.